2006
DOI: 10.1002/pros.20533
|View full text |Cite
|
Sign up to set email alerts
|

Promoter hypermethylation of GSTP1, AR, and 14‐3‐3σ in serum of prostate cancer patients and its clinical relevance

Abstract: Hypermethylation of TSG can be detected in serum of prostate cancer patients. Some hypermethylated TSG can be detected in serum of healthy controls. GSTP1 was not detectable in controls and correlated significantly with Gleason score and stage of disease. Therefore, this gene may be a promising new tool in prostate cancer diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 23 publications
1
51
1
Order By: Relevance
“…Consistent with most previous observations in prostate tumor tissue and blood ( Jeronimo et al, 2004;Yegnasubramanian et al, 2004;Reibenwein et al, 2007;Sunami et al, 2009;Steiner et al, 2010), we found that elevated DNA methylation levels in prostate tumor tissues were related to worse clinicopathological outcomes. Specifically, GSTP1, p16 (CDKN4A), and APC methylation levels were significantly associated with higher Gleason score.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with most previous observations in prostate tumor tissue and blood ( Jeronimo et al, 2004;Yegnasubramanian et al, 2004;Reibenwein et al, 2007;Sunami et al, 2009;Steiner et al, 2010), we found that elevated DNA methylation levels in prostate tumor tissues were related to worse clinicopathological outcomes. Specifically, GSTP1, p16 (CDKN4A), and APC methylation levels were significantly associated with higher Gleason score.…”
Section: Discussionsupporting
confidence: 92%
“…Our hypermethylation frequency of GSTP1 was somewhat higher than those reported by other groups [12][13][14][15]18]. These differences maybe explained by different detection methods and/or differences in the study cohort: Bastian et al used also a restriction endonuclease method and detected GSTP1 hypermethylation in 12% of serum samples from PCA patients in a screening cohort with US-Americans.…”
Section: Discussioncontrasting
confidence: 70%
“…RARB2 and GSTP1methylation were also correlated with the AJCC stage [82]. GSTP1 hypermethylation was the strongest predictor of PSA recurrence following radical prostatectomy [83] and it was correlated with the Gleason score and the extent of metastasis in patients with hormone-refractory PCA [84].…”
Section: Prostate Cancermentioning
confidence: 89%